Shortcuts to inner peace : 70 simple paths to everyday serenity - Bush, Ashley Davis (Berkley Trade, 2011)
Finding serenity every day...in the everyday things we do. It can be a challenge to reach a calm and relaxed mindset, especially in our modern world. But in Shortcuts to Inner Peace, Ashley Davis Bush helps readers learn how to hit the pause button amidst the chaos with a spirit of mindfulness-linking fast, easy, and restorative respites to ordinary everyday activities.